Not so fast: The impact of impulsivity on weight loss varies by treatment type. (1st June 2017) - Manasse, Stephanie M.; Flack, Daniel; Dochat, Cara; Zhang, Fengqing; Butryn, Meghan L.; Forman, Evan M.
Abstract: Behavioral weight loss (BWL) treatments result in suboptimal weight losses for many individuals. Impulsivity appears to be a maintenance factor of obesity, yet few studies have examined impulsivity as a predictor of outcomes from BWL. We examined specific facets of impulsivity (inhibitory control and delay discounting) as moderators of outcome in BWL. Overweight adults (n = 190) were randomized to standard behavioral treatment (SBT) or acceptance-based behavioral treatment (ABT). We hypothesized that impulsivity would be inversely associated with weight loss, and that the association between impulsivity and outcome would be attenuated in the ABT condition. Poorer general inhibitory control predicted lower percent weight lost at 12 months across conditions at the trend level ( b = −0.003, p = 0.06). The negative impact of low inhibitory control on weight loss was attenuated by assignment to ABT versus SBT ( b = 0.004, p = 0.03). Treatment condition, at trend level, also moderated the impact of delay discounting ( b = −0.011, p = .098) and food-specific inhibitory control ( b = 0.003, p = 0.06) on percent weight loss such that those with greater impulsivity benefitted most from ABT. Results reveal a potential pattern that impulsivity reduces benefit derived from SBT but not ABT. Further research on the moderating effect of impulsivity is necessary to inform the development of targeted treatments for clinically meaningful subtypes of patients.